Manoel Bomfim : trajetória, suas críticas e concepções sobre Brasil como nação - Santos, Ivan Paulo Silveira (2017)
This dissertation aims to analyze the background and the train of thought of Manoel Bomfim about the formation of the Brazilian nation. Thus, this study has three analyses perspectives: a) the family and author‟s life path b) his academic formation and constitution as intellectual and c) the reflection about the work “A América Latina: males da origem”. The family origin gains importance as the author comes from a social group with no strain. Besides the status, the academic qualification in Medicine had great influence in the use of a “biologizing” language, with several medical metaphors. A constant association between “biological” and “social” phenomena. The academic background allowed him to have some social contacts that has introduced him to be part of some Brazilian “intellectual groups” at the turn of the nineteenth and twentieth centuries. In these groups, Bomfim took part in the discussions that occurred during that period, hugely featured on racial issues. Regarding these issues, the author stood being very critical, disagreeing with racial assumptions, such as “bleaching”. Thereby, he assumed a different attitude from most of his intellectual peers and the institutions which they represented. In short, in the review of Bomfim‟s first work, we find his basic ideas which he will develop on his later works. And one of them is that the “evils” of the Latin Americans nations are linked to the inherited issues of the “parasitic” European colonization. Such inheritance, in addition to promoting the spoliation of these colonized societies, produced “conservative” nations. It means that, societies who reproduced by “inheritance” the “habits” of the colonizers. From these questionings about Latin America‟s socioeconomic conditions as the result from its “origin” and “ethinicity”, Bomfim proposed another conception of nation and nationality by questioning the scientific speeches from that time.